Trace-element geochemistry of molybdenite from porphyry Cu deposits of the Birgilda-Tomino ore cluster (South Urals, Russia) - Plotinskaya, O.; Abramova, V.; Groznova, E.; Tessalina, Svetlana; Seltmann, R.; Spratt, J. (Mineralogical Society, 2018)
Minerallogical, electron microprobe analysis and laser ablation-inductively coupled plasma-mass spectrometry data from molybdenite within two porphyry copper deposits (Kalinovskoe and Birgilda) of the Birgilda-Tomino ore cluster (South Urals) are presented.† The results provide evidence that molybdenites from these two sites have similar trace-element chemistry. Most trace elements (Si, Fe, Co, Cu, Zn, Ag, Sb, Te, Pb, Bi, Au, As and Se) form mineral inclusions within molybdenite. The Re contents in molybdenite vary from 8.7 ppm to 1.13 wt.%. The Re distribution within single molybdenite flakes is always extremely heterogeneous. It is argued that a temperature decrease favours the formation of Re-rich molybdenite. The high Re content of molybdenite observed points to a mantle-derived source.